Laparoscopic versus open distal pancreatectomy (LAPOP): study protocol for a single center, nonblinded, randomized controlled trial - Björnsson, Bergthor (Trials, 2019)
BACKGROUND: Earlier nonrandomized studies have suggested that laparoscopic distal pancreatectomy (LDP) is advantageous compared with open distal pancreatectomy (ODP) regarding hospital stay, blood loss, and recovery. Only one randomized study has been conducted showing reduced time to functional recovery after LDP compared with ODP. METHODS: LAPOP is a prospective randomized, nonblinded, parallel-group, single-center superiority trial. Sixty patients with lesions in the pancreatic body or tail that are found by a multidisciplinary tumor board to need surgical resection will be randomized to receive LDP or ODP. The primary outcome variable is postoperative hospital stay, and secondary outcomes include functional recovery (defined as no need for intravenous medications or fluids and as the ability of an ambulatory patient to perform activities of daily life), perioperative bleeding, complications, need for pain medication, and quality of life comparison. DISCUSSION: The LAPOP trial will test the hypothesis that LDP reduces postoperative hospital stay compared with ODP. TRIAL REGISTRATION: ISRCTN, 26912858. Registered on 28 September 2015. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13063-019-3460-y) contains supplementary material, which is available to authorized users.